IMPLEMENTASI LESSON STUDY UNTUK MENINGKATKAN KEMAMPUAN PROFESONALISME GURU DALAM PEMBELAJARAN BAHASA INGGRIS - Lia Amelia (STAI Nurul Falah Airmolek, 2022)
English is very important especially when it comes to education. In addition, through English we can introduce the cultural and linguistic diversity of this nation to those who naturally want to know about this nation. English is very much needed in the national and international arena. Learning English is not difficult so it's easy to understand. Lesson study appears as an alternative to overcome problems in the teaching and learning process, as learning from the learning process to create more practical and effective learning. This article uses a qualitative descriptive method. Qualitative descriptive is a way of uncovering and studying data from books, offline and online articles and other sources and explaining a phenomenon, event, current event, and describing a picture or painting in a systematic, factual and accurate manner regarding facts, characteristics properties in the form of relationships between the phenomena investigated, so that researchers can extract important data and write it down in this article. The results of the research are knowing how the application of lesson study can increase teacher professionalism in learning English so that teachers become more professional in explaining their duties.